2013
DOI: 10.1016/j.ajpath.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Improve Nephrocalcinosis but Not Dystrophic Cardiac Calcinosis in DBA/2 Mice

Abstract: Nephrocalcinosis is characterized by aberrant deposition of calcium in the kidneys and is seen in phosphate nephropathy, primary hyperparathyroidism, and distal renal tubular acidosis. To further evaluate the specific pathophysiologic role of T cells in ectopic calcification, we used DBA/2 mice that are prone to develop nephrocalcinosis and dystrophic cardiac calcinosis. Female DBA/2 mice were depleted of T cells (n = 10) or regulatory T cells (Tregs) (n = 15) using either an anti-CD3ɛ or an anti-CD25 monoclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
(36 reference statements)
2
12
0
Order By: Relevance
“…In our model, we do not need surgical interventions and the mortality of these mice is very low (5 to 10%; data not shown) since we stop HPD on day 4 or 7, respectively. As shown previously, mortality increases rapidly in our mice when fed with HPD for more than 10 days [ 19 ]. Of note, choosing the DBA/2 strain is of critical importance to induce CKD, since C57BL/6 mice do not develop critical calcification neither in the kidney nor in the cardiovascular system [ 20 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our model, we do not need surgical interventions and the mortality of these mice is very low (5 to 10%; data not shown) since we stop HPD on day 4 or 7, respectively. As shown previously, mortality increases rapidly in our mice when fed with HPD for more than 10 days [ 19 ]. Of note, choosing the DBA/2 strain is of critical importance to induce CKD, since C57BL/6 mice do not develop critical calcification neither in the kidney nor in the cardiovascular system [ 20 ].…”
Section: Discussionsupporting
confidence: 80%
“…From our data, we cannot clearly tell, whether the mice also develop concentric left ventricular hypertrophy since we have low ( n ) numbers in echocardiography and heart weights did not differ between the groups. In HPD-induced acute kidney injury model due to phosphate nephropathy, we found the picture of dystrophic cardiac calcinosis resulting in the significantly increased mortality in the mice [ 19 ]. In the presented CKD model, the cardiac picture looked differently since we did not detect relevant calcifications in the myocardium (data not shown), but preliminary observations by echocardiography showed that the mice developed some extent of cardiac hypertrophy probably due to hypertension which more closely resembles the human CKD-MBD phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrocalcinosis could be considered to be a passive phenomenon resulting from deposition of a supersaturated phosphate product associated with tissue remodeling and ultimately leading to the loss of functioning renal parenchyma. It has been demonstrated that acute phosphate nephropathy can be actively modulated by inflammatory repair mechanisms, suggesting a role for regulatory T cells (27). However, the mechanistic details in many of the pathological situations resulting in ectopic calcium deposition in kidney remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Within 5–14 days mice develop calcification within the Tunica media of the aorta, which is more pronounced in the abdominal part of the aorta mimicking the situation in ESRD patients ( 14 ). Whereas inflammation is of crucial importance in the development of renal calcification ( 13 ), vascular media calcification does not seem to be dependent on immune cells ( 14 ).…”
Section: Introductionmentioning
confidence: 99%